Respuesta :

leena

Hello!

[tex]\large\boxed{f^{-1} = \frac{5x+2}{4x-2}, f^{-1}(3) = \frac{17}{10} }[/tex]

[tex]f(x) = \frac{2x +2}{4x - 5}[/tex]

Find the inverse by swapping the x and y variables:

[tex]y = \frac{2x +2}{4x - 5}\\\\x = \frac{2y +2}{4y - 5}[/tex]

Begin simplifying. Multiply both sides by 4y - 5:

[tex]x(4y - 5) = 2y + 2[/tex]

Start isolating for y by subtracting 2 from both sides:

[tex]x(4y - 5) -2 = 2y[/tex]

Distribute x:

[tex]4yx - 5x - 2 = 2y[/tex]

Move the term involving y (4yx) over to the other side:

[tex]- 5x - 2 = 2y - 4yx\\\\[/tex]

Factor out y and divide:

[tex]- 5x - 2 = y(2 - 4x)\\\\y = \frac{-5x-2}{-4x+2} \\\\y = \frac{-(5x + 2)}{-(4x - 2)} \\\\y^{-1} = \frac{5x + 2}{4x - 2}[/tex]

Use this equation to evaluate [tex]f^{-1}(3)[/tex]

[tex]f^{-1}(3) = \frac{5(3) + 2}{4(3) - 2} = \frac{17}{10}[/tex]

ACCESS MORE